2013
DOI: 10.1016/j.neurobiolaging.2012.08.009
|View full text |Cite
|
Sign up to set email alerts
|

CCL2 affects β-amyloidosis and progressive neurocognitive dysfunction in a mouse model of Alzheimer's disease

Abstract: Neuroinflammation affects the pathobiology of Alzheimer’s disease (AD). Notably, beta-amyloid (Aβ) deposition induces microglial activation and the subsequent production of pro-inflammatory neurotoxic factors. In maintaining brain homeostasis, microglia plasticity also enables phenotypic transition between toxic and trophic activation states. One important control for such cell activation is through the CC-chemokine ligand 2 (CCL2) and its receptor, the CC-chemokine receptor 2 (CCR2). Both affect microglia and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
63
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 66 publications
4
63
0
Order By: Relevance
“…Accumulating evidence has revealed that inflammatory responses mediated by MCP-1 were linked to Aβ pathology and microglia accumulations,26 and that peripheral MCP-1 may attract the blood-derived monocytes migrating to CNS 27. Meta-analysed results also demonstrated remarkably increased α1-ACT levels in both the peripheral and CSF of AD compared with the control, which were both in tight associations with dementia progression 28 29.…”
Section: Discussionmentioning
confidence: 97%
“…Accumulating evidence has revealed that inflammatory responses mediated by MCP-1 were linked to Aβ pathology and microglia accumulations,26 and that peripheral MCP-1 may attract the blood-derived monocytes migrating to CNS 27. Meta-analysed results also demonstrated remarkably increased α1-ACT levels in both the peripheral and CSF of AD compared with the control, which were both in tight associations with dementia progression 28 29.…”
Section: Discussionmentioning
confidence: 97%
“…A similar observation was made in APP/PS1*CB2 À/À mice that expressed reduced levels of CCL2 compared to APP/PS1 mice. CCL2 is responsible for the recruitment of macrophages and microglia during CNS inflammation (Shi and Pamer, 2011), and the brains of CCL2-deficient APP/PS1 mice possessed fewer microglia (Kiyota et al, 2013). This suggests that the reduced microgliosis observed in APP/PS1*CB2 À/À mice could be due to reductions in CCL2 expression resulting in an impaired ability to recruit peripheral macrophages into the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…In AD, CCL2 levels are elevated in plasma, cerebrospinal fluid and the brain (Ishizuka et al, 1997; Sun et al, 2003). While Aβ stimulates microglia and astrocytes leading to CCL2 production (El Khoury et al, 2003), deficiencies of CCL2 and its ligand binding receptor, CCR2, underlie disease onset and tempo (El Khoury et al, 2007; Kiyota et al, 2013; Naert and Rivest, 2011). Such findings strongly support a role for chemokine signaling in AD pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Such findings strongly support a role for chemokine signaling in AD pathogenesis. Indeed, CCL2 deficiency accelerates impairments in hippocampal neurogenesis, learning and memory in AD mice overexpressing human APP and PS1 with FAD mutations (Kiyota et al, 2013). …”
Section: Introductionmentioning
confidence: 99%